The importance of cash flow analysis - Ševkušić Ljubiša; Bodiroga Radomir (Trendovi u Poslovanju)
For the economy of the Republic of Serbia, agriculture is a very relevant branch. Its significance and its place is reflected in the fact that in the creation of GDP it participates with about 6,5%. This percentage is significantly increased if one takes into account that agriculture contributes greatly to the development of other sectors of the economy, primarily to producers and processors of inputs and raw materials. In addition, it is characterized by a relatively high employee share, significant natural, technical, technological and other potentials. However, regardless of the mentioned potentials, it is evident that agricultural enterprises in Serbia do not realized the business results expected of them. For this reason, before the management, a big task which is reflected in making business decisions, which will significantly contribute to the successful operation of these companies. Significant and very useful information for the realization of the give task provides analysis of cash flows. In this regard, the main goal of the work is to look at and point out the usefulness of information obtained by analyzing cash flows. The results of the research show that the analysis of cash flows significantly enriches the information base, which significantly facilitates the decision-making and management process of the company.